Between familiarity and exoticism: Tourists’ and locals’ attitudes to Cyrillic signage in Karlovy Vary’s linguistic landscape - Lisek, Grzegorz (Studia Rossica Posnaniensia, 2026)
The present article posits the argument that in Karlovy Vary the social meaning of Russian Cyrillic has undergone a shift from its former status as a routine tourist resource to a marked, politically charged symbol. This study builds on the findings of research in the field of linguistic landscapes, which has historically placed significant emphasis on the production of signs. The present study proposes an audience-centred evaluation of how scripts are read and assessed in the post-pandemic era, with a particular focus on the consequences of the 2022 Russian invasion of Ukraine. A sample of 100 residents and tourists (50% of each group) were invited to rate eight photographed signs (six in Cyrillic and two in English) from commercial, institutional and commemorative settings on 7-point scales (familiarity, exoticism, legibility, overall evaluation) and to report their script proficiency. Across domains, English/Latin signage was judged to be significantly more familiar and legible and less exotic than Cyrillic. The residents’ perception of Cyrillic was that it was more ordinary than that of the tourists, yet both groups treated English as the unmarked international code. The enhancement of Cyrillic literacy led to an increase in familiarity; however, it did not eliminate the “exoticity premium”, which was most pronounced in institutional and commemorative contexts. These findings document a symbolic re-evaluation of Russian in Central Europe and demonstrate the analytical value of integrating perception measures into linguistic landscape studies.